Interventional sialendoscopy for treatment of juvenile recurrent parotitis - Celeste Gary; Evelyn A Kluka; Barry Schaitkin; Rohan R Walvekar (Wolters Kluwer Medknow Publications, 2011)
Objective: To evaluate our preliminary experience with interventional sialendoscopy for the diagnosis and treatment of juvenile recurrent parotitis (JRP). Materials and Methods: Three consecutive pediatric patients with JRP who underwent interventional sialendoscopy were identified. Interventional sialendoscopy consisted of serial dilation of the Stenson's duct, endoscopy of the ductal system and saline irrigation followed by instillation of triamcinolone acetate. Clinical, demographic, procedure-related data and complications were documented. End points of the study were technical success, defined as completion of the procedure, subjective improvement in symptoms as indicated by the patients or their parents and assessment of safety in terms of complications. Results: Three male patients with a mean age of 9 years (range 6-11 years) underwent interventional sialendoscopy for JRP. Endoscopic findings included a blanched stenotic duct with intraductal debris in those who were symptomatic. Technical success was 100%. The mean number of episodes of JRP in the year prior to presenting to our service among the three patients was 5 (range 4-6 per year). There were no new episodes of JRP reported at the last follow-up. There were no major complications. Conclusion: Our preliminary experience concurs with the current literature and suggests that interventional sialendoscopy is effective for the management of JRP and can be considered for patients who fail conservative medical management.